2001
DOI: 10.1034/j.1399-6576.2001.450816.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol and gastric effects of morphine

Abstract: Propofol did not abolish morphine-induced delay of gastric emptying even if propofol abolished the decrease of gastric tone induced by morphine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Both endogenous and administered opiates, acting via m receptors, may contribute to abnormal upper gastrointestinal motor function [20,21]. Specifically, opiate administration in the critically ill is associated with delayed gastric emptying [3] possibly due to fundal relaxation [22], reduced antral contractions [23] and increased phase 3 frequency [24]. A number of other sedative agents also affect gastrointestinal motility [25][26][27][28][29][30][31][32], however neuromuscular blocking agents appear to have no effect [11].…”
Section: Gastric Emptying In the Critically Illmentioning
confidence: 99%
“…Both endogenous and administered opiates, acting via m receptors, may contribute to abnormal upper gastrointestinal motor function [20,21]. Specifically, opiate administration in the critically ill is associated with delayed gastric emptying [3] possibly due to fundal relaxation [22], reduced antral contractions [23] and increased phase 3 frequency [24]. A number of other sedative agents also affect gastrointestinal motility [25][26][27][28][29][30][31][32], however neuromuscular blocking agents appear to have no effect [11].…”
Section: Gastric Emptying In the Critically Illmentioning
confidence: 99%
“…With an inhalation technique without opioids, the effect of inhalation agents on gastric motility may cease quickly after discontinuation of the agent [3]. An intravenous technique with an ultra-shortacting opioid, to minimize the negative opioid effect on motility, combined with propofol, which has antiemetic properties, and to some degree, antagonizes the opioid effect on gastric motility [4], may favor motility. Both methods are, theoretically, optimal for gastric motility.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in volunteers have shown that this dose of propofol does not influence gastric tone (155), and it was given at least 30 min before the study started. The intragastric bag was folded carefully around the gastric tube and positioned in the gastric fundus via oral intubation.…”
Section: Methodsmentioning
confidence: 99%
“…Penagini found that morphine increased gastric tone (172), while Hammas reported a decrease in gastric tone (155). Both studies used the same dose of intravenous morphine (0.1 mg/kg) and both used a gastric barostat.…”
Section: Effects Of Remifentanil On Gastric Tone (Iii)mentioning
confidence: 99%